PERSEPSI GURU TENTANG PENGELOLAAN SARANA PENDIDIKAN DI SMA NEGERI SE KECAMATAN BASA AMPEK BALAI TAPAN - Yeza Putri Zahri; Ermita Ermita; Rusdinal Rusdinal; Widiawati Widiawati (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe teachers' perceptions of educational facility management in public senior high schools in Basa Ampek Balai Tapan District, covering aspects of procurement, utilization, maintenance, inventory, and supervision. The study used a quantitative descriptive approach. The study population consisted of 92 teachers from public senior high schools in Basa Ampek Balai Tapan District, with a sample of 78 teachers selected using proportional random sampling techniques. The research instrument was a Likert scale questionnaire that had been tested for validity and reliability. Data were analyzed using the average technique (mean). The results showed that teachers' perceptions of educational facility management were generally in the good category with an average score of 4.13. The procurement aspect obtained an average score of 3.80 (good), utilization 3.44 (sufficient), maintenance 4.56 (good), inventory 4.47 (good), and supervision 4.40 (good). The maintenance aspect was the indicator with the highest score, while utilization received the lowest score. These findings indicate that the management of educational facilities in schools has been running well, but the utilization of facilities still needs to be improved so that the available facilities can be used optimally to support the learning process.